Self-supported carbon nanofibers as negative electrodes for K-ion batteries: Performance and mechanism. (1st December 2020) - Touja, Justine; Gabaudan, Vincent; Farina, Filippo; Cavaliere, Sara; Caracciolo, Laure; Madec, Lénaïc; Martinez, Hervé; Boulaoued, Athmane; Wallenstein, Joachim; Johansson, Patrik; Stievano, Lorenzo; Monconduit, Laure
Abstract: Self-standing carbon nanofibers (CNF) were electrospun and tested in K-ion batteries (KIB). The comparison of the electrochemical performance of KIB using potassium bis(fluorosulfonyl)imide (KFSI) and potassium hexafluorophosphate (KPF6 ) carbonate-based electrolytes revealed that, despite the coulombic efficiency is more readily stabilized with KFSI than with KPF6, the long-term cycling is quite the same, with a specific capacity of 200 mAh.g −1 for the CNF electrode. Post-mortem X-ray photoelectron spectroscopy analysis shows a more stable solid electrolyte interphase (SEI) for KIB employing KFSI. Finally, the K + ion storage mechanism was investigated by combining cyclic voltammetry and operando Raman spectroscopy, showing a combination of adsorption and intercalation processes. The rate capability is, however, better with the KPF6 salt due to SEI layers formed at both CNF and K metal electrode, highlighting that full cell may lead to even superior results.